Computed tomographic assessment of optic foramen - Ajay Kumar,; Rajesh KS,; Jyoti A,; Amita M,; Vandana M, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
A detailed morphometric study of optic foramen was conducted in the CT scans of 30 adult patients. The quantitative and qualitative parameters were observed. The transverse diameter (TD), the vertical diameter (VD) and the distance of optic foramen to apex of petrous temporal bone were measured as quantitative parameters. The qualitative parameters measured were shape, margin and confluence. The frequency of range of transverse and vertical diameters was also observed. A comparison was made between right and left sided morphometric values. The mean transverse diameter of optic foramen was found to be greater on right side, whereas mean vertical diameter was observed to be greater in left sided optic foramen.